Initiating reading in Creole: Contents and contexts of primers in the Danish West Indies, 1770–1825 - Appel, Charlotte; Bakker, Peter; Robbe, Joost (Scandinavian Studies in Language, 2024)
In the eighteenth and early nineteenth centuries, Danish and German missionaries in the Danish West Indies produced educational materials for converted enslaved adults and their children. Over nearly a century, these missionaries used the local Dutch Creole for instruction, with five printed primers, or ABC books, surviving from this period. In this article, we focus on these five primers, used to initiate reading and religious teaching, including a newly discovered primer in Creole dated 1782. This recently discovered primer is compared with two other Lutheran primers in the same language, printed in 1770, compiled by Kingo and Wold, as well as with two later, nearly identical ones (dated 1800 and 1825), produced by the Moravian Brethren and printed in Germany. The analysis begins with an exploration of the physical attributes, structure, and contents of these publications. Next, they are contextualized within the broader historical framework of catechism primers (Juska-Bacher et al. 2023), schooling and of colonial teaching (Grenby 2023a, 2023b).